Genome and Transcriptome Sequencing of Populus × sibirica Identified Sex-Associated Allele-Specific Expression of the CLC Gene - Pushkova, Elena N.; Krasnov, George S.; Lakunina, Valentina A.; Novakovskiy, Roman O.; Povkhova, Liubov V.; Dvorianinova, Ekaterina M.; Beniaminov, Artemy D.; Fedorova, Maria S.; Snezhkina, Anastasiya V.; Kudryavtseva, Anna V.; Dmitriev, Alexey A.; Melnikova, Nataliya V. (Frontiers in Genetics, 2021)
Transcriptome sequencing of leaves, catkin axes, and flowers from male and female trees of Populus x sibirica and genome sequencing of the same plants were performed for the first time. The availability of both genome and transcriptome sequencing data enabled the identification of allele-specific expression. Such an analysis was performed for genes from the sex-determining region (SDR). P. x sibirica is an intersectional hybrid between species from sections Aigeiros (P. nigra) and Tacamahaca (P. laurifolia, P. suaveolens, or P. x moskoviensis), therefore, a significant number of heterozygous polymorphisms were identified in the SDR that allowed us to distinguish between alleles. In the SDR, both allelic variants of the TCP (T-complex protein 1 subunit gamma), CLC (Chloride channel protein CLC-c), and MET1 (DNA-methyltransferase 1) genes were expressed in females, while in males, two allelic variants were expressed for TCP and MET1 but only one allelic variant – for CLC. Targeted sequencing of TCP, CLC, and MET1 regions on a representative set of trees confirmed the sex-associated allele-specific expression of the CLC gene in generative and vegetative tissues of P. x sibirica. Our study brings new knowledge on sex-associated differences in Populus species.